EP207/#318 A retrospective study of ovarian cancer among elderly – evaluation and prognosis. (4th December 2022) - Brezis, Miriam; Hasson, Shira Peleg; Shachar, Eliya; Grisaro, Dan; Laskov, Ido; Michaan, Nadav; Adar, Lyri; Harpaz, Avigail; Diner, Adi; Levy, Bar; Wolf, Ido; Safra, Tamar
Abstract : Objectives: Half of epithelial ovarian cancer (EOC) are diagnosed above age 65. Women over 70 have higher morbidity and mortality. Our real-life retrospective study evaluates elderly with EOC. Methods: Women above 70 were classified as 'elderly' (N=233) (71–93), and bellow 70 – 'control cohort' (N=755) (24–70). Treatment schedule used (6–8 cycles) were 3-weekly regimen (PC-3W) – carboplatin AUC-6 + Paclitaxel 175 mg/m 2 on day 1 of a 21-day cycle, and weekly regimen (PC-1W) – carboplatin AUC-2 + paclitaxel 80 mg/m 2 on days 1, 8, and 15 of a 28-day cycle Results: When comparing elderly to control median overall survival (mOS) was 41.26 (33.05–63.87) vs. 69.78 (50.07–75.01) months respectively (p<0.0001). No statistical differences were shown when comparing toxicities except for grade 2 anemia – 36.49% vs. 19.67% respectively (p<0.0001) and grade 2 alopecia – 44.81% vs. 60.52% respectively (p<0.0001). The use of PC-1W vs. PC-3W was 44.29% vs 47.14% in the elderly compared to 39.03% vs. 60.3% in the control (p<0.0001). Among the elderly mOS was 57.17 vs. 30.00 months for PC-1W and PC-3W respectively (p = 0.0075). No differences in toxicity were shown, when comparing PC-1W to PC-3W in elderly except for grade 2 alopecia – 26.21% vs. 65.18% respectively (p<0.0001), and grade 2 neuropathy – 20.19% vs. 36.61% respectively (p=0.0119) Conclusions mOS is reduced in elderly, though better than expected, furthermore toxicity is tolerable in elderly. PC-1W was both more abundant and had better mOS in elderly. Therefore PC-1W regimen may offer advantages for elderly in terms of tolerance while retaining efficacy